From macroalgae to porous graphitized nitrogen-doped biochars – Using aquatic biota to treat polycyclic aromatic hydrocarbons-contaminated water. (May 2020) - Cheng, Hu; Ji, Rongting; Bian, Yongrong; Jiang, Xin; Song, Yang
Graphical abstract: Highlights: Macroalgae-derived PGNBCs were prepared and characterization. The PGNBCs exhibited high sorption capabilities to PAHs. Possible sorption mechanisms were explained by kinetic and isotherm studies. Abstract: Enhanced macroalgal biochars with large specific surface areas (up to 399 m 2 g −1 ), partly graphitized structure, high nitrogen doping (up to 6.14%), and hydrophobicity were fabricated by co-carbonization of macroaglae, ferric chloride, and zinc chloride. These biochars were used as sorbents for the removal of polycyclic aromatic hydrocarbons from water. The sorption capacity of polycyclic aromatic hydrocarbons onto macroalgal biochars was high (up to 90 mg g −1 ), and recycling by thermal desorption was practicable. We revealed the physical-dominated multilayer sorption process, based on results from characterization and sorption experiments. Pore filling, mass transfer, π–π stacking, and the partition effect were found to be possible sorption mechanisms. This study suggests that porous graphitized nitrogen-doped biochars may be synthesized from macroalgae with simple one-pot carbonization and display promising applicability for sorption removal of organic pollutants from water.